Bimbingan Pranikah Mempersiapkan Pemahaman Calon Pengantin Mewujudkan Keluarga Sakinah, Mawaddah, Warahmah - Muksin, Ucin; Saepulrohim, Asep; Ananda, Elvira Nur (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
Premarital guidance for the sake of creating a samawa family is the ambition of every newlywed and a dream for those who have married. Therefore, this study aims to determine the program, understanding, and stages of premarital guidance in realizing the Samawa family. The research method used in this study is descriptive qualitative. The results of this study indicate that premarital guidance in KUA Cibarusah District Bekasi regency there are two programs, namely government programs and independent programs. Understanding to the bride and groom because in the material that has been delivered by the speaker can be understood and understood by the participants. In the research, there are stages that are carried out, namely the pre-implementation stage, the implementation stage, the question and answer stage and the last closing stage.